2012
DOI: 10.1038/nphys2262
|View full text |Cite
|
Sign up to set email alerts
|

Probing Planck-scale physics with quantum optics

Abstract: One of the main challenges in physics today is to merge quantum theory and the theory of general relativity into a unified framework. Researches are developing various approaches towards such a theory of quantum gravity, but a major hindrance is the lack of experimental evidence of quantum gravitational effects. Yet, the quantization of space-time itself can have experimental implications: the existence of a minimal length scale is widely expected to result in a modification of the Heisenberg uncertainty relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
656
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 608 publications
(674 citation statements)
references
References 60 publications
12
656
2
Order By: Relevance
“…The pulsed measurements performed here may also be utilized for a QND-measurement-based lightmechanics quantum interface [53]. Furthermore, a sequence of four pulsed optomechanical interactions can be used to generate non-classical mechanical states of motion via an optomechanical geometric phase [54] and can even be used to experimentally explore potential quantum-gravitational phenomena [55].…”
Section: Discussionmentioning
confidence: 99%
“…The pulsed measurements performed here may also be utilized for a QND-measurement-based lightmechanics quantum interface [53]. Furthermore, a sequence of four pulsed optomechanical interactions can be used to generate non-classical mechanical states of motion via an optomechanical geometric phase [54] and can even be used to experimentally explore potential quantum-gravitational phenomena [55].…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of active cooling is that it is possible to realize the ground state for the bad cavity condition given by ω eff ≪ κ [36]. This condition is also required to probe spacetime using pulsed light [13].…”
mentioning
confidence: 99%
“…Progress towards this quantum regime is underway [2,[8][9][10] in the field of cavity optomechanics [11] particularly in the bad cavity regime, where the optical linewidth is broader than that of the mechanical resonance. Although the bad cavity condition is often not promising in terms of coherence because of the slow mechanical oscillation, it enables us to detect gravitational-waves [12], and potentially to probe deformed commutators [13,14], generate entangled states [15][16][17], and test wavefunction collapse models [18][19][20][21][22]. …”
mentioning
confidence: 99%
“…Also the author studied in [20] its effects on the weak equivalence principle (WEP) and the Liouville theorem (LT) in statistical mechanics, and it was found that the GUP can potentially explain the small observed violations of the WEP in neutron interferometry experiments [21] and also predicts a modified invariant phase space which is relevant to the Liouville theorem. Recently, it was suggested in [22] that the GUP can be measured directly in Quantum Optics Lab which confirm the theoretical predictions in [16,18] The proposals for the existence of extra dimensions has opened up new doors of research in quantum gravity [23][24][25][26]. In particular, a host of interesting work is being done on different aspects of low-energy quantum gravity phenomenology.…”
Section: Introductionmentioning
confidence: 83%